Penyuluhan dan Sosialisasi Fatwa MUI No. 32 Tahun 2022 Tentang Pelaksanaan Ibadah Kurban Saat Kondisi Wabah Penyakit Mulut Dan Kuku - Apriantoro, Muhamad Subhi; Al-Kahfi, M. Ammar Mujahidy; Ananda, Widiva Febri (JRCE (Journal of Research on Community Engagement), 2023)
This activity aims to provide counseling and socialization of MUI Fatwa No. 32 of 2022 concerning sacrifices during an epidemic of mouth and nail disease. This is important to do considering the lack of public information regarding guidelines for the implementation of qurbani from animal selection, quarantine to standardized slaughter according to Islamic law, especially during the outbreak of mouth and nail diseases that attack split-toed/even hoofed animals such as cattle, buffalo, sheep, goats, deer, camels, and includes wild animals such as elephants, antelopes, bison, deer, and giraffes. Community service was carried out at the Al-Hidayah Taklim Council, Ngasem Village, Colomadu District, Karanganyar Regency, Central Java with 50 participants. Prior to the activity, participants were given a pre-test to measure basic understanding of the sacrificial procedure, then a post-test was conducted to measure changes in understanding after technical socialization is carried out. The results of this activity showed an increase in people's understanding of the procedure for sacrificing from elections, quarantine, to slaughtering sacrificial animals and how the MUI fatwa no. 32 of 2022 can be applied as a reference in the implementation of sacrifice in the midst of an outbreak of mouth and nail disease in sacrificial animals.